You want us to do that without first defining a,

**k**,**c**, or d? Followup: Your definitions answer your question...1 Answers · Science & Mathematics · 22/09/2018

...(+) + e ---> Na E = -2.71V

**K**(+) + e --->**K**E = -2.93V Rb(+) + e ---> Rb E = -2.93V Cs (+) + e ---> Cs E = -2.92V From the above values...4 Answers · Science & Mathematics · 27/04/2007

...intercept), you use the equation b^2-4ac=0. You plug in 20 for b, 25 for a, and

**k**for**c**. You get: 625-80k=0. Then you can add 80k to both sides to...2 Answers · Education & Reference · 07/08/2008

...induction - first take n = 0 then we have sum (i = 0) =

**C**(**k**-1,**k**-1) = 1 =**C**(**k**,**k**) so the result is correct...**k**)!**k**]/[**k**!(m+1)!] =(m+1+**k**)!/[**k**!(m+1)!] =**C**(m+1+**k**,**k**) so the formula also holds for n = m+1 ...1 Answers · Science & Mathematics · 09/04/2008

... that, you don't care about absolute zero. A temperature difference in

**K**or**C**is the same measurement. (Ditto for Fahrenheit and ...2 Answers · Science & Mathematics · 11/06/2017

1) E = 1 – ( c / k ) … assuming that’s what you mean Multiplying both sides by... (√5) But neither of those is simpler than the original c ) 4√b / [(√3) – b] Rationalizing the denominator by multiplying...

2 Answers · Science & Mathematics · 16/01/2015

dT/dt = k ( C - T) ∫ dT / ( C - T) = ∫ k dt - ln...(t)= Ae^(-kt) + C T(0)= Ae^(- k (0)) + C = 100 A + C = 100 C = -A + 100 T...

6 Answers · Science & Mathematics · 26/06/2008

The x-intercept occurs when y = 0 -

**k**/**c**= log_a(d(x - h)) d(x - h) = a^(-**k**/**c**) x = [a^(-**k**/**c**)]/d + h1 Answers · Science & Mathematics · 15/11/2015

... 6C2 = 15 ways. In general, there are (m+ k -1) C ( k -1) ways. So if n > (m+ k -1) C ( k -1) then at least 2 ...

1 Answers · Science & Mathematics · 06/02/2020

0

**K**> 0 F > 0**C**273**K**= 0**C**32 F = 0**C**0**C**= 0**C**1 Answers · Science & Mathematics · 05/07/2011